PENGARUH PENGGUNAAN PUPUK BERSUBSIDI DAN LUAS LAHAN TERHADAP JUMLAH PRODUKSI JAGUNG DI DESA WATUDAMBO DUA KECAMATAN KAUDITAN (The Effect of Subsided Fertilizer Use and Land Area On The Total Corn Production in Watutambo Dua Village, Kauditan District) - Guntur Barnabas Rarun; Theodora M. Kathiandagho; Olly Esry Laoh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
The purpose of this study was to determine the effect of the use of subsidized fertilizers and harvested area on corn productivity in Watudambo Dua Village, Kauditan District, either simultaneously or partially. The research method used was quantitative method with 70 corn farmers in Watudambo Village as respondents. Based on the results of research using multiple linear regression analysis, it is known that the use of subsidized fertilizers and harvested area have a positive influence on the amount of corn production in Watudambo Dua Village. Simultaneously, the use of subsidized fertilizers and harvested area have a significant positive effect on the amount of corn production in Watudambo Dua Village, Kauditan District. Extensive land and supported by the use of appropriate fertilizers can directly provide optimal results for the amount of corn production. Partially subsidized fertilizer use did not significantly affect corn productivity in Watudambo Dua Village although it has a positive direction. This condition is caused by the allocation of subsidized fertilizer provided by the government does not meet the demand for subsidized fertilizer by farmers. This situation makes farmers reduce the dose of fertilizer and fertilization time. Harvested area partially has a significant effect on the amount of corn production. The larger the land area, the more corn that can be planted. With optimal land use by farmers can encourage an increase in harvested area.